Screening of Different Eggplant Cultivars against Wilt Disease Caused by Fungi, Bacteria and Nematodes - Akhter Hossain2 and Lutfunnaher Laila3, Md. Ashrafur Rahman1*, Farjana Ali2, K.M (Journal of Experimental Sciences, 2011)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> An experiment was conducted in the Field of Sher-e-Bangla Agricultural University, Dhaka to screen out the resistant cultivars of eggplant against wilt disease. Eight cultivars viz. Nayantara, Singhnath, Dhundul, Kazla, Marich Begun Luffa, Kata Begun and Uttara were used as treatments. At 55 days after transplanting (DAT) the cultivar Luffa exhibit the highest bacterial wilt incidence (80%) and the lowest wilt incidence was recorded in the cultivar Kata Begun (30%). At 90 DAT the highest Fusarium and Nemic wilt incidence was recorded in the cultivar Luffa and the lowest wilt incidences were recorded in the cultivar Kata Begun. The highest shoot height was recorded in the cultivar Kata Begun and the lowest shoot height was recorded in the cultivar Singhnath. The highest gall number was recorded in the cultivar Luffa and the lowest gall number was recorded in the cultivar Kata Begun. The highest yield per hectare (29.84 t/ha) was recorded in the cultivar Nayantara and the lowest yield (10.50 t/ha) was recorded in the cultivar Dhundhul. Among the cultivars Kata Begun graded as resistant for both Bacterial, Fungal and Nemic wilt. Ã‚Â 